Identifying the main actors and their positions on international forest policy issues in Argentina - Burns, Sarah L; Giessen, Lukas (BOSQUE, 2017)
Since the Earth Summit in Rio in 1992, forest management and conservation have become important issues in international forest-related politics and policies. As a result, different international initiatives have dealt with the subject directly or indirectly, building up a fragmented international forest regime complex made of international laws and agreements about forests. The diverse elements of this regime complex are differently made relevant by various actors in different countries. The aim of this study was to identify the most relevant forest issue elements in Argentina as well as the main involved actors and their positions towards these elements as a result of their interests. To identify the issues, content analysis of documents was employed on public sources (newspapers, websites) as well as expert sources (personal interviews and professional journals) from 2008 - 2012. The most relevant actors were identified and categorized. The positions of the different actors were obtained analyzing the different sources. The forest issue elements found to be relevant in Argentina are: climate change and forests, forest biodiversity, regional forest-related policy initiatives, competing forest certification schemes, desertification, bilateral forest related disputes and forest-related support by international organizations. The various actors identified showed different positions regarding a diversity of issues, being climate change and forests the most conflictive concern among actors, especially among environmental NGOs and forestry associations and the Secretariat of Environment and Sustainable Development and the Ministry of Agriculture, Livestock and Fisheries.